1999
DOI: 10.1074/jbc.274.20.14325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gα13 as One of the G-proteins That Couple to Human Platelet Thromboxane A2 Receptors

Abstract: Previous studies have shown that ligand or immunoaffinity chromatography can be used to purify the human platelet thromboxane A 2 (TXA 2 ) receptor-G␣ q complex. The same principle of co-elution was used to identify another G-protein associated with platelet TXA 2 receptors. It was found that in addition to G␣ q , purification of TXA 2 receptors by ligand (SQ31,491)-affinity chromatography resulted in the co-purification of a member of the G 12 family. Using an antipeptide antibody specific for the human G 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 58 publications
1
53
0
1
Order By: Relevance
“…To investigate such a mechanism, platelet aggregation was studied using an aggregometer. Platelet response to U46619 is mediated by two different receptors or by the same receptor with two different affinities as follows: one binding site that binds U46619 with high affinity that mediates platelet shape change, Ca 2ϩ increase, and cortactin tyrosine phosphorylation (15)(16)(17), and a second binding site that binds U46619 with low affinity and mediates platelet aggregation, inositol-phosphate production, and protein kinase C activation (18 -20). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate such a mechanism, platelet aggregation was studied using an aggregometer. Platelet response to U46619 is mediated by two different receptors or by the same receptor with two different affinities as follows: one binding site that binds U46619 with high affinity that mediates platelet shape change, Ca 2ϩ increase, and cortactin tyrosine phosphorylation (15)(16)(17), and a second binding site that binds U46619 with low affinity and mediates platelet aggregation, inositol-phosphate production, and protein kinase C activation (18 -20). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that either TXA 2 has two distinct TP receptors on platelets or, alternatively, two different affinity states of the same receptor may exist as follows: one of high affinity that mediates platelet shape change, Ca 2ϩ mobilization, and cortactin tyrosyl phosphorylation, and a second of low affinity that mediates PKC activation and platelet aggregation (15)(16)(17)(18)(19)72). Because U46619-induced platelet shape change and calcium increase was preserved by RPAI-1, it was clear that the high affinity TP receptor on platelet membrane was not the target of RPAI-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas many of the latter reported studies have implicated various G protein α subunits in mediating TP activation [45][46][47][48][49][50][51][52][53][54][55] and the latter studies [33,60] mobilization by TPα and TPβ indicating that the TP isoforms may mediate opening of L-type channels in a Gα 12 dependent signalling mechanism [61]. Taken together, these studies investigating the signalling by the TP isoforms indicate that both TPα and TPβ couple to both the G q and G 12 family with no apparent isoform specific differences in their signalling behaviour.…”
Section: Tp Isoform Signallingmentioning
confidence: 99%
“…Two GPCRs for ADP, the P2Y1 and P2Y12 receptors, stimulate the G q and G i signalling pathways, respectively, and their co-stimulation is needed for ADP-induced primary aggregation [9][10][11][12]. The thromboxane A # receptor also couples to G q , as well as G "# and G "$ [13], but requires agonists secreted from platelets for activation of G i pathways and aggregation [7]. Thrombin activates a family of G-protein-coupled protease-activated receptors (PARs).…”
Section: Introductionmentioning
confidence: 99%